Malaysia: nation, state, politics and elections - a brief survey / Munis Paran - Paran, Munis (Faculty of Communication and Media Studies (FCMS), 1994)
Any attempt to provide a brief survey of a multi-faceted subjects as that of the growth on a nation-state, with all its attending paraphernalia, is a frightening one. The words of caution found in Lucian Pye's presidential address on 2 September 1989 at the 85th annual meeting of the American Political Science Association in Atlanta come to mind "As a part of our confusion over scientific and humanistic knowledge we tend regularly to vacillate between favouring the one over the other. Indeed, the subfields are usually at different phases in what seem to be steady pendulum swings between the universal and the particular, theory and description, parsimony and thick description".